A comprehensive profile and analysis of special education researches in DLSU-Manila from 1999 to 2016: A pioneer study - Rueda, Anna Marisol V. (Animo Repository, 2018)
This study established a comprehensive profile and analysis of the research studies produced by the Masters of Arts in Education major in Special Education program at the De La Salle University – Manila over its seventeen years of running from 1999 to 2016. A total of 113 research studies were examined and analyzed using Qualitative Content Analysis to determine categories and identify themes to give a broad description in terms of the content in terms of what research areas were focused on, what population groups were studied, which methods were used, and what results and recommendation it yielded. The results of the study showed that the most preferred area the researches focused on was mental retardation. The researches also placed great importance in studying special education teachers as population. The most utilized method was descriptive research – survey type. In terms of research problems, the studies aimed mostly at teachers and their perceptions, attitudes, teaching strategies and personal and professional factors. The trend in terms of the investigated topics overtime was also determined. Additionally, enduring issues such as imbalance in areas of research was noted. Significant recommendations were given to help the special education program and department for the direction of their future research studies.